Study the effect of Capparis Spinosa fruit extract on fasting blood sugar, lipid profile and BMI of Iraqi diabetic and obese patients (Journal of the College of Basic Education, 2019)
Objective: DMT 2 is the common metabolic disorders with highly impact on quality of life. The tsability of C. Spinosa fruits extract in reducing plasma glucose levels and serum lipids was tested . There is no study about the anti-diabetic , anti- obesity effect of capparis spinosa fruits in Iraq . Therefore, we aim to study the effects of the C. spinosa fruits on diabetic obese patients.